1980
DOI: 10.1039/p19800001462
|View full text |Cite
|
Sign up to set email alerts
|

Base catalysed rearrangements involving ylide intermediates. Part 4. [1,3] Sigmatropic rearrangements of 4-dimethylaminobutenes and [3,3] sigmatropic rearrangements of 3-dimethylaminohexa-1,5-dienes

Abstract: The [1,3] sigmatropic rearrangement (1 1) + (1 2) of the 9-dimethyIamino-9-(1 -phenylallyl)fluorene is a stereoselective process (84 : 16) at 170". Analogous [1,3] rearrangements (1 6) + (1 7) of other fluorene derivatives show that the reaction rate is increased by electron donating 9-substituents in the order 0-> NMe, > OMe. Similar substituent effects are observed for the [3,3] Cope rearrangement (25) + (26) of hexa-1,5-dienes. 4-Pheny1, 4,4-dimethyl, and 3-dimethylamino substituents are particularly effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…As representative examples, both Rautenstrauch (9) and Baldwin (10) have shown that treatment of benzyl allyl ether 1 with nBuLi gives rise to a mixture of [2,3]-and [1,2]-products 2 and 3 respectively, with increased [1,2]-product observed at higher temperatures. Although not widely recognised, sporadic control reactions have demonstrated the feasibility of converting [2,3]-Wittig products to [1,2]-Wittig products (formally via a [1,3]-rearrangement), although the generality, mechanism and configurational consequence has not been established (11)(12)(13)(14)(15)(16). The concerted or dissociative (via ionic or radical intermediates) nature of both the [1,2]and [1,3]-processes has been much debated.…”
mentioning
confidence: 99%
“…As representative examples, both Rautenstrauch (9) and Baldwin (10) have shown that treatment of benzyl allyl ether 1 with nBuLi gives rise to a mixture of [2,3]-and [1,2]-products 2 and 3 respectively, with increased [1,2]-product observed at higher temperatures. Although not widely recognised, sporadic control reactions have demonstrated the feasibility of converting [2,3]-Wittig products to [1,2]-Wittig products (formally via a [1,3]-rearrangement), although the generality, mechanism and configurational consequence has not been established (11)(12)(13)(14)(15)(16). The concerted or dissociative (via ionic or radical intermediates) nature of both the [1,2]and [1,3]-processes has been much debated.…”
mentioning
confidence: 99%